PENGHEMATAN BIAYA PERSEDIAAN OBAT MENGGUNAKAN METODE HYBRID DI RSIA PERDANA MEDICA SURABAYA - Astri Widya Krisyunita; Achmad Djunawan; Khoirul Umam (Journal of Health Service Management, 2022)
Background: Based on drugs inventories data at pharmacy unit Perdana Medica Maternal and Child Hospital Surabaya in March 2020, 35 items of drugs and medical devices were expired and damaged. In addition, stock out caused an Rp11,295,500.00 profit loss (estimated). Based on these problems, research is needed to find how much savings can be achieved in planning the procurement of drugs using the hybrid method. Objective: Find out how much savings can be made by RSIA Perdana Medica in planning the procurement of drugs using the hybrid method. Methods: This research is quantitative descriptive research. The ABC-VED method is used to classify drug inventories based on their use and investment levels. Inventory policy is searched using the hybrid method by comparing actual costs with expected total costs. Result: Perdana Medica Maternal and Child Hospital could save Rp4,440,457.85 expenses based on the calculation results. Conclusion: The hybrid method can be used as a new method in inventory planning at Perdana Medica Maternal and Child Hospital.